EDUCATIONAL ACTIVITY AS A FACTOR IN SOLVING MATHEMATICAL PROBLEMS OF ELEMENTARY SCHOOL STUDENTS THROUGH THE THEORY OF COGNITIVE EDUCATION - Zaynab Abdusattarova (Web of Journals Publishing, 2024)
The article is devoted to the study of interrelationships in improving the ability to solve mathematical problems by organizing the educational activities of elementary school students using the theory of cognitive education. Questionnaires were conducted with 45 4th-grade students to check their educational activities through the observation method. In order to assess mathematical problem-solving skills, problem descriptions were used to conduct the research. The test results showed a significant correlation between academic performance and mathematical problem-solving skills. With the help of cognitive learning theory, learning activities were tested and correlational results were determined in solving mathematical problems. Based on the results of the analysis, we can conclude that it has a significant effect on the educational activity and ability to solve mathematical problems of the fourth-grade elementary school students of Boyovut district, Sirdarya region.
Keywords: mathematical problem-solving skills, problem descriptions